Pemberdayaan ekonomi masyarakat Kepenghuluan Bagan Manunggal Kabupaten Rokan Hilir melalui pembuatan produk yoghurt berbasis buah – buahan lokal - Irda Sayuti; Darmawati Darmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Community service activities have been carried out in the form of local fruit-based yoghurt making techniques from Bagan Manunggal Village, Bagan Sinembah sub-district, Rokan Hilir Regency. This activity is an application of the use of appropriate technology with Biotechnology to the community which aims to empower the economy of the local community through processing fruits into yoghurt. Service activities are carried out in two stages, namely; the socialization stage to the community, the training phase and guidance on making yoghurt from fruits. The socialization phase was conducted in collaboration with the village government and the PKK Kepenghuluan Bagan Manunggal Driving Team. The training phase is carried out with direct demonstration methods, guidance and open discussion related to making Yogurt from local fruits. The results of this activity are obtained by Yogurt products in the form of Pineapple Yogurt, Salak Yogurt, Jackfruit Yogurt, Banana Yogurt, and Dragon Fruit Yogurt.